Identification of three novel subgroups within the X-disease group phytoplasma associated with strawberry redness disease - Fernandez, Franco Daniel; Meneguzzi, Natalia; Conci, Luis Rogelio (2017)
Strawberry plants showing symptoms of lethal redness disease were found in production fields located in Tucumán province, Argentina. The presence of phytoplasmas was confirmed by PCR of 16S rDNA gene using phytoplasma universal primers. According to the 16S rDNA gene sequence identity, the four isolates analysed are related to the X-disease group (16SrIII) (identity ~99 %). These results were confirmed by in silico RFLP, actual RFLP and also by phylogenetic analyses of the 16S rDNA gene. This new phytoplasma was named as Strawberry X-Redness (StrawXR).